Application of Mathematical Models for Optimizing Inspection Frequency in Maintenance and Management of Pavement - Khabiri, Mohammad Mehdi; Ghafoori Fard , Zohreh (Journal of Science and Technology, 2021)
Mathematical optimization, also called mathematical programming, is the process by which the best answer (according to a set of criteria) is selected from a set of possible answers to a particular problem. Today, optimization problems are used in all quantitative fields such as computer science, engineering, operations research, economics, and more; one of the engineering disciplines in which optimization is very important is road and transportation engineering. Road repair is one of the most important components of pavement management that requires regular road inspection by road specialists. One of the most important measures to prevent failure is maintenance inspection; Assessment of the condition of road surfaces to ensure their performance, while the road still provides maximum safety for existing traffic, should be done to ensure timely and effective repair and reconstruction operations. But exactly when these inspections should take place and when they are effective is an issue that is addressed in this study. The aim of this study is to optimize the frequency of maintenance inspections for a high-traffic suburban road by optimizing the frequency of inspections with a certain degree of reliability; so, the breakage function was considered as a pavement condition index (PCI). The results show that in order to pave the suburban road with high traffic in order to perform the desired pavement with 95% reliability, 218 inspections should be carried out annually (on average once every two days).